Sharing Space: The Presence of Other Bodies Extends the Space Judged as Near. - Chiara Fini; Marcello Costantini; Giorgia Committeri (PLoS ONE, 2014)
BACKGROUND:As social animals we share the space with other people. It is known that perceived extension of the peripersonal space (the reaching space) is affected by the implicit representation of our own and other's action potentialities. Our issue concerns whether the co-presence of a body in the scene influences our extrapersonal space (beyond reaching distance) categorization. METHODOLOGY/PRINCIPAL FINDINGS:We investigated, through 3D virtual scenes of a realistic environment, whether egocentric spatial categorization can be influenced by the presence of another human body (Exp. 1) and whether the effect is due to her action potentialities or simply to her human-like morphology (Exp. 2). Subjects were asked to judge the location ("Near" or "Far") of a target object located at different distances from their egocentric perspective. In Exp. 1, the judgment was given either in presence of a virtual avatar (Self-with-Other), or a non-corporeal object (Self-with-Object) or nothing (Self). In Exp. 2, the Self condition was replaced by a Self-with-Dummy condition, in which an inanimate body (a wooden dummy) was present. Mean Judgment Transition Thresholds (JTTs) were calculated for each subject in each experimental condition. Self-with-Other condition induced a significant extension of the space judged as "Near" as compared to both the Self-with-Object condition and the Self condition. Such extension was observed also in Exp. 2 in the Self-with-Dummy condition. Results suggest that the presence of others impacts on our perception of extrapersonal space. This effect holds also when the other is a human-like wooden dummy, suggesting that structural and morphological shapes resembling human bodies are sufficient conditions for the effect to occur. CONCLUSIONS:The observed extension of the portion of space judged as near could represent a wider portion of "accessible" space, thus an advantage in the struggle to survive in presence of other potential competing individuals.